How Stressed are Students and What Can We Do About It? Findings from a Self-report Survey of Contract Cheating Behaviours and the Stressful Events College Students Experience - Ferguson, Corrine D.; Toye, Margaret A.; Eaton, Sarah Elaine (Canadian Perspectives on Academic Integrity, 2023)
Empirical research on contract cheating in Canada has been limited (Eaton, 2022) and tends to focus on the university (Eaton, 2019; Stoesz & Los, 2019; Thacker, 2022) while there has been relatively little research on academic integrity and contract cheating in community colleges and other non-university higher education institutions (Bretag & Harper, 2020). To address this gap, in 2021, researchers collected data on student engagement in academic integrity violation behaviour and the stress they experienced as they were completing their programs at one Canadian community college. Using self-report survey methodology and utilizing students as partners in research, we found students engaged in a variety of contract cheating behaviours, and experienced a myriad of stressful events both in and outside the college context, including traumatic life events. In this presentation, we explore the link between stress and contract cheating behaviour and address how we can respond at all levels of our institutions to better support students and promote academic integrity.